Literature and liberation five essays from Southeast Asia - Thumboo, Edwin (Manila, Philippines solidaridad Pub. House, 1988)
Contents: The price of freedom/ Ee Tiang HOng - - Art, life, and the Filipino soul/ F. Sionil Jose - - An awareness of self and society/ Mochtar Lubis - - Siamese literature and social liberation/ Sulak Sivaraksa - - History, language, paradigms, lacunae/ Edwin Thumbo
Includes bibliographies
Keywords: Southeast Asian Literature -- 20th century -- Political aspects; Revolutionary literature, Southeast Asian -- History and criticism; National liberation movements -- Southeast Asia